Teologi Pendamaian dalam Surat Filemon Sebagai Resolusi Keterputusan Kekeluargaan “Mardomu di Tano Rara” Batak Toba - Silalahi, Haposan; Sibarani, Yosua (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
Abstract. Unresolved conflict in the Batak Toba community can lead to the severance of family relation with the emergence of the statement,